BiFeO3 / MoSe2 photocatalytic materials, their preparation methods, and applications.
By preparing BiFeO3/MoSe2 composite materials, the problem of high electron-hole recombination rate in BiFeO3 photocatalytic materials was solved, thereby improving photocatalytic activity and selectivity. The formation of compact interfaces and strong interfacial interactions promoted charge separation and improved photocatalytic performance.
Patent Information
- Application Number
- CN202310815697.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2043-07-04
AI Technical Summary
Existing BiFeO3 photocatalytic materials suffer from reduced activity due to high electron-hole recombination rates, and the Co3O4/BiFeO3 composite material has poor dispersion and few active centers, resulting in insufficient photocatalytic activity.
BiFeO3/MoSe2 composite materials were prepared by hydrothermal method, forming a compact interface and strong interfacial interactions, which inhibited electron-hole recombination, promoted charge separation, and improved photocatalytic activity.
The photocatalytic selectivity and activity of the BiFeO3/MoSe2 composite material were significantly improved, the separation and transfer rate of photogenerated carriers were enhanced, and the photocatalytic performance was improved.
Smart Images

Figure CN116851011B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalytic materials technology, specifically relating to BiFeO3 / MoSe2 photocatalytic materials, their preparation methods, and applications. Background Technology
[0002] Hydrogen peroxide (H2O2), commonly known as hydrogen peroxide solution, is a promising clean chemical widely used in environmental treatment, medical sterilization, electronics, and chemical synthesis. H2O2 is highly water-soluble, easy to store and transport, and its only byproduct is H2O, making it an environmentally friendly oxidant and a next-generation sustainable energy carrier. Currently, the industrial anthraquinone process for producing H2O2 faces sustainability challenges, such as high energy consumption, complex industrial routes, and harmful byproducts. Semiconductor photocatalysis technology, requiring only H2O, O2, and light energy, and possessing advantages such as being pollution-free and having abundant reserves, is considered one of the most promising H2O2 synthesis technologies.
[0003] In semiconductor photocatalytic materials, Bi-based photocatalysts such as Bi₂MoO₆ (Colloids Surf, A, 648(2022)129363) and BiVO₄ (J.Environ.Chem.Eng, 9(2021)105973) are widely used due to their suitable band gap and low cost. However, these photocatalysts are susceptible to the high recombination rate of electrons and holes, leading to a decrease in their activity. Bismuth ferrite (BiFeO₃), as a perovskite bimetallic oxide, has a defect structure that effectively overcomes the disadvantage of high electron-hole recombination rate, and is widely used in pollutant degradation, water disinfection, H₂ generation, and CO₂ reduction. However, its catalytic performance is limited by electron transfer capacity, resulting in relatively low photoactivity of pure BiFeO₃ catalysts.
[0004] The solution to this problem is usually to construct composite materials. For example, Chinese invention patent application No. 201811171248.9 discloses a Co3O4 / BiFeO3 heterojunction photocatalyst. However, the composite photocatalyst material composed of Co3O4 and BiFeO3 deposited on the surface has defects such as poor dispersion and few exposed active functional groups and active centers, which are not conducive to the separation and transfer of photogenerated carriers. In addition, it has defects such as few active functional groups and few reactive sites. Therefore, modifying it on BiFeO3 cannot significantly improve the separation and transfer rate of photogenerated carriers, and there are still problems such as insufficient photocatalytic activity. Summary of the Invention
[0005] In order to overcome the shortcomings and deficiencies of the prior art, the primary objective of this invention is to provide a method for preparing BiFeO3 / MoSe2 photocatalytic materials.
[0006] Another object of the present invention is to provide a BiFeO3 / MoSe2 photocatalytic material prepared by the above preparation method.
[0007] Another object of the present invention is to provide the application of the above-mentioned BiFeO3 / MoSe2 photocatalytic material.
[0008] The primary objective of this invention is achieved through the following technical solution:
[0009] A method for preparing a BiFeO3 / MoSe2 photocatalytic material involves a hydrothermal method to form a compact, polycrystalline interface between BiFeO3 and MoSe2 with strong interfacial interactions. This process suppresses the recombination of photogenerated electron-hole pairs, promotes charge separation between different crystal planes, and enhances photocatalytic activity. The method includes the following steps:
[0010] (1) Preparation of BiFeO3:
[0011] Bismuth nitrate pentahydrate and ferric nitrate nonahydrate were dispersed in a mixture of nitric acid and ethylene glycol, then stirred in a constant temperature water bath and ground into powder. The resulting powder was then calcined in a muffle furnace to obtain BiFeO3.
[0012] (2) Preparation of BiFeO3 / MoSe2 photocatalytic material:
[0013] Sodium molybdate is added to distilled water and stirred at room temperature to form a sodium molybdate solution, wherein the mass concentration of sodium molybdate in distilled water is 7-9 g / L;
[0014] Selenium powder and hydrazine hydrate are mixed and stirred at room temperature to form a selenium powder solution, wherein the mass concentration of selenium powder in hydrazine hydrate is 14-18 g / L.
[0015] First, sodium molybdate solution is added to sodium molybdate solution. Then, BiFeO3 is added dropwise to the mixture of selenium powder solution and sodium molybdate solution. The mixture is ultrasonically stirred. After stirring, the mixture is transferred to a 100 mL polytetrafluoroethylene-lined autoclave and heated. After washing and drying, the mixture is obtained. The mass concentration of BiFeO3 in sodium molybdate solution is 10–16.67 g / L.
[0016] In step (1), the water bath temperature is 60-80℃ and the time is 10-14h;
[0017] In step (1), the calcination temperature is 500-550℃ and the time is 2-4 hours;
[0018] In step (1), the mass concentrations of bismuth nitrate pentahydrate and ferric nitrate nonahydrate in nitric acid are 200–400 g / L and 200–400 g / L, respectively;
[0019] The mass concentration of the nitric acid solution in step (1) is 933–1065 g / L;
[0020] In step (1), the volume ratio of nitric acid to ethylene glycol is 1:1;
[0021] In step (2), the volume ratio of sodium molybdate solution to selenium powder solution is 3:1;
[0022] In step (2), the stirring time at room temperature and ambient temperature is 10-30 min, and the ultrasonic stirring time is 20-40 min;
[0023] In step (2), the heating temperature is 200–220°C and the heating time is 20–24 hours.
[0024] In step (2), the drying temperature is 60-80℃ and the time is 10-12h.
[0025] A BiFeO3 / MoSe2 composite photocatalytic material was prepared by the above-described preparation method.
[0026] Application of the BiFeO3 / MoSe2 composite photocatalyst in hydrogen peroxide synthesis.
[0027] Specifically, 0.2–0.8 g / L of BiFeO3 / MoSe2 composite photocatalyst material was added to deionized water containing ethylene glycol. After stirring and injecting oxygen in the dark at room temperature to reach adsorption equilibrium, the reaction was carried out for 60 min under visible light irradiation and oxygen supply.
[0028] In the above steps, the preferred ratio of ethylene glycol to deionized water is 1:19, and the amount of BiFeO3 / MoSe2 composite photocatalyst added to the wastewater is 0.5 g / L.
[0029] The mechanism of this invention is as follows: Pure MoSe2 exhibits a smaller work function and a higher Fermi energy than pure BiFeO3. When BiFeO3 and MoSe2 are in close contact, electrons in BiFeO3 spontaneously flow to MoSe2 until their Fermi energies reach the same level. Due to the loss of electrons, the interface region on the BiFeO3 side becomes positively charged, leading to the formation of an electron depletion region and the downward bending of the BiFeO3 band edge. Conversely, the interface region near MoSe2 becomes negatively charged, leading to the formation of an electron accumulation layer and the upward bending of the MoSe2 band edge. Therefore, an internal electric field is formed at the interface of the BiFeO3 / MoSe2 heterojunction, which prevents the continuous flow of electrons from BiFeO3 to MoSe2. Under light irradiation, both BiFeO3 and MoSe2 transition to excited states through excited electrons from the valence band to the conduction band. Then, driven by Coulomb interaction and the internal electric field, the electrons accumulated in the conduction band of BiFeO3... - h in the valence band of MoSe2+ During recombination, electrons accumulate in the conduction band of MoSe2 and then react with O2 to generate H2O2. Furthermore, the oxygen vacancies enriched in BiFeO3 facilitate the adsorption and activation of O2, which lowers the total activation energy barrier for O2.
[0030] Compared with the prior art, the present invention has the following significant effects:
[0031] (1) The BiFeO3 / MoSe2 composite photocatalytic material prepared in this invention can greatly improve the photocatalytic selectivity and activity of the BiFeO3 / MoSe2 composite photocatalytic material by introducing oxygen vacancies and adjusting the electronic structure. Since BiFeO3 and MoSe2 form a compact interface and have strong interfacial interaction, it is beneficial to the transport of photogenerated carriers between the composites, which can suppress the recombination of photogenerated electron-hole pairs and improve the photocatalytic activity.
[0032] (2) The unique nanoflower morphology of MoSe2 increases the active sites of BiFeO3 / MoSe2 composite photocatalyst. In addition, the unique 1T / 2H combination of MoSe2 gives BiFeO3 / MoSe2 composite photocatalyst semiconductor and metallic properties, thereby improving photocatalytic performance.
[0033] (3) The BiFeO3 / MoSe2 composite photocatalyst material is polycrystalline, which can realize charge separation between different crystal planes, greatly improve the separation and transfer rate of photogenerated carriers, and thus improve the photocatalytic performance of the BiFeO3 / MoSe2 composite photocatalyst material.
[0034] (4) The BiFeO3 / MoSe2 composite photocatalyst material prepared by this invention has the advantages of being green and economical, having good stability and high catalytic activity. It is a novel composite photocatalyst material with a novel structure and excellent performance. Attached Figure Description
[0035] Figure 1 This is a transmission electron microscope (TEM) image of the BiFeO3 / MoSe2 material of this invention.
[0036] Figure 2 The X-ray diffraction analysis diagrams are of the pure BiFeO3, MoSe2, and BiFeO3 / MoSe2 composite visible light catalytic materials of this invention.
[0037] Figure 3 The photoluminescence spectra of the pure BiFeO3, MoSe2, and BiFeO3 / MoSe2 composite visible light catalytic materials of this invention are shown.
[0038] Figure 4The diagram shows the effect of synthesizing H2O2 using pure BiFeO3, MoSe2, and BiFeO3 / MoSe2 composite visible light catalytic materials of the present invention. Detailed Implementation
[0039] The present invention will be described in detail below with reference to embodiments, so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.
[0040] This invention provides a method for preparing a BiFeO3 / MoSe2 photocatalytic material, comprising the following steps:
[0041] (1) Preparation of BiFeO3:
[0042] Bismuth nitrate pentahydrate and ferric nitrate nonahydrate were dispersed in a mixture of nitric acid and ethylene glycol, then stirred in a constant temperature water bath and ground into powder. The resulting powder was then calcined in a muffle furnace to obtain BiFeO3.
[0043] (2) Preparation of BiFeO3 / MoSe2 photocatalytic material:
[0044] Sodium molybdate is added to distilled water and stirred at room temperature to form a sodium molybdate solution, wherein the mass concentration of sodium molybdate in distilled water is 7-9 g / L;
[0045] Selenium powder and hydrazine hydrate are mixed and stirred at room temperature to form a selenium powder solution, wherein the mass concentration of selenium powder in hydrazine hydrate is 14-18 g / L.
[0046] First, sodium molybdate solution is added to sodium molybdate solution. Then, BiFeO3 is added dropwise to the mixture of selenium powder solution and sodium molybdate solution. The mixture is ultrasonically stirred. After stirring, the mixture is transferred to a 100 mL high-pressure autoclave lined with polytetrafluoroethylene and heated. After washing and drying, the mixture is obtained. The mass concentration of BiFeO3 in sodium molybdate solution is 10-16.67 g / L.
[0047] Preferably, the water bath temperature in step (1) is 60-80°C and the time is 10-14 hours.
[0048] Preferably, the calcination temperature in step (1) is 500-550°C and the time is 2-4 hours.
[0049] Preferably, in step (1), the mass concentrations of bismuth nitrate pentahydrate and ferric nitrate nonahydrate in nitric acid are 200–400 g / L and 200–400 g / L, respectively.
[0050] Preferably, the mass concentration of the nitric acid solution in step (1) is 933–1065 g / L.
[0051] Preferably, the volume ratio of nitric acid to ethylene glycol in step (1) is 1:1.
[0052] Preferably, in step (2), the volume ratio of sodium molybdate solution to selenium powder solution is 3:1.
[0053] Preferably, in step (2), the stirring time at room temperature and ambient temperature is 10-30 min, and the ultrasonic stirring time is 20-40 min.
[0054] Preferably, the heating temperature in step (2) is 200-220°C and the heating time is 20-24 hours.
[0055] Preferably, the drying temperature in step (2) is 60-80°C and the drying time is 10-12 hours.
[0056] The present invention also provides a BiFeO3 / MoSe2 composite photocatalytic material, which is prepared by the above preparation method.
[0057] This invention also provides an application of BiFeO3 / MoSe2 composite photocatalyst material in hydrogen peroxide synthesis.
[0058] Unless otherwise specified, the materials and instruments used in the following embodiments are commercially available, the processes used are conventional, and the equipment used is conventional.
[0059] Example 1:
[0060] 3.88 g of bismuth nitrate pentahydrate and 3.23 g of ferric nitrate nonahydrate were dispersed in a mixture of 20 mL of 2M nitric acid and 20 mL of ethylene glycol. The mixture was then stirred in a constant temperature water bath at 80 °C for 12 h and ground into powder. The resulting powder was calcined in a muffle furnace at 500 °C for 2 h to obtain BiFeO3 (labeled as S1).
[0061] Example 2:
[0062] 0.24195 g of sodium molybdate was added to 30 mL of distilled water and stirred at room temperature for 20 min to form a sodium molybdate solution. 0.17592 g of selenium powder was mixed with 10 mL of hydrazine hydrate and stirred at room temperature for 20 min to form a selenium powder solution. This solution was then added to the sodium molybdate solution and ultrasonically stirred for 20 min. The mixture was then transferred to a 100 mL polytetrafluoroethylene-lined autoclave and heated at 220 °C for 24 h. After washing, it was dried at 80 °C for 12 h to obtain MoSe2 (labeled as S2).
[0063] Example 3:
[0064] The operation process is the same as in Example 2, except for the following differences;
[0065] The 0.3 g BiFeO3 solution described in step (1) was added dropwise to a mixture of selenium powder solution and sodium molybdate solution. This yielded a 0.3-BiFeO3 / MoSe2 composite photocatalyst material (labeled S3) with uniform morphology and visible light photocatalytic performance.
[0066] Example 4:
[0067] The operation process is the same as in Example 2, except for the following differences;
[0068] The 0.4 g BiFeO3 solution described in step (1) was added dropwise to a mixture of selenium powder solution and sodium molybdate solution. This yielded a 0.4-BiFeO3 / MoSe2 composite photocatalyst material (labeled S4) with uniform morphology and visible light photocatalytic performance.
[0069] Example 5:
[0070] The operation process is the same as in Example 2, except for the following differences;
[0071] The 0.5 g BiFeO3 solution described in step (1) was added dropwise to a mixture of selenium powder solution and sodium molybdate solution. This yielded a 0.5-BiFeO3 / MoSe2 composite photocatalyst material (labeled S5) with uniform morphology and visible light photocatalytic performance.
[0072] Figure 1 This is a TEM image of the BiFeO3 / MoSe2 composite visible light photocatalyst material. Figure 1 It is known that the nanosheets have a planar spacing of 0.284 nm, corresponding to the (100) plane of MoSe2. Furthermore, the lattice spacing of 0.278 nm is attributed to BiFeO3, corresponding to the (110) hexagonal pattern. A compact interface is formed between BiFeO3 and MoSe2. In addition, the BiFeO3 / MoSe2 composite visible light photocatalyst material exhibits triangular and honeycomb lattice regions, corresponding to the coexistence of the 1T and 2H phases in BiFeO3 / MoSe2, confirming the presence of both phases.
[0073] Figure 2 XRD patterns of pure BiFeO3, MoSe2, and BiFeO3 / MoSe2 composite visible light photocatalysts are shown. Figure 2It can be seen that pure BiFeO3 exhibits typical characteristic diffraction peaks at 22.49°, 31.81°, 32.14°, 39.51°, 45.81°, 51.38°, and 57.01°, corresponding to the (012), (104), (110), (202), (024), (116), and (214) crystal planes of BiFeO3. Pure MoSe2 shows main peaks at 13.70°, 31.42°, 37.88°, 47.49°, and 55.92°, corresponding to the (002), (100), (103), (105), and (110) crystal planes, respectively. The diffraction peak observed at 13.6° in MoSe2 provides evidence for its layered crystal structure, characterized by weak van der Waals interactions between the Se-Mo-Se layers. Furthermore, compared to BiFeO3, the BiFeO3 / MoSe2 material exhibits a shift of all diffraction peaks to lower angles due to the significant interfacial interactions induced by MoSe2. This effect can be attributed to MoSe2's attack on O embedding within MoSe2 via Se, resulting in a larger interlayer distance.
[0074] Figure 3 The PL diagrams for pure BiFeO3, MoSe2, and BiFeO3 / MoSe2 composite visible light photocatalysts are shown below. Figure 3 It can be seen that S4 has the lowest luminescence intensity compared with BiFeO3 and MoSe2, indicating that the combination of BiFeO3 and MoSe2 inhibits the combination of photogenerated carriers, increases the number of effectively photogenerated electrons and holes, and thus improves the photocatalytic performance of the composite material.
[0075] Example 6:
[0076] Take 50 mg of S1, S2, S3, S4, and S5 respectively and add them to 95 mL of deionized water and 5 mL of ethylene glycol, mix thoroughly, inject oxygen in the dark and stir for 30 min to allow the photocatalytic materials to reach adsorption equilibrium. Then, subject the resulting mixture to photocatalytic reaction for 60 min under visible light with a wavelength λ > 420 nm. During the photocatalytic reaction, take 1 mL of the reaction solution every 10 min, according to 2Ce 4+ +H₂O₂→2Ce 3+ +2H + The +O2 equation, where the yellow Ce 4+ It will be reduced to colorless Ce by H2O2 3+ The number of moles of H2O2 is determined by measuring the amount of Ce consumed. 4+ The yield of H2O2 is determined by the number of moles. A calibration curve is obtained using UV-Vis spectroscopy, and the yield of H2O2 is calculated. The results are as follows: Figure 4 As shown.
[0077] Figure 4This is a comparison chart showing the catalytic efficiency of pure BiFeO3, MoSe2, and BiFeO3 / MoSe2 composite visible light photocatalysts for hydrogen peroxide production under visible light conditions. Figure 4 It can be seen that after 60 minutes of illumination, the S4 of the present invention has the highest efficiency in producing hydrogen peroxide under visible light conditions, which indicates that the BiFeO3 / MoSe2 composite photocatalyst material of the present invention can effectively synthesize hydrogen peroxide.
[0078] The embodiments described above are preferred embodiments of the present invention, but the present invention is not limited to the above embodiments. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing BiFeO3 / MoSe2 photocatalytic materials, characterized in that, Includes the following steps: (1) Preparation of BiFeO3: Bismuth nitrate pentahydrate and ferric nitrate nonahydrate were dispersed in a mixture of nitric acid and ethylene glycol, then stirred in a constant temperature water bath and ground into powder. The resulting powder was then calcined in a muffle furnace to obtain BiFeO3. (2) Preparation of BiFeO3 / MoSe2 photocatalytic materials: Sodium molybdate is added to distilled water and stirred at room temperature to form a sodium molybdate solution, wherein the mass concentration of sodium molybdate in distilled water is 7-9 g / L; Selenium powder and hydrazine hydrate are mixed and stirred at room temperature to form a selenium powder solution, wherein the mass concentration of selenium powder in hydrazine hydrate is 14-18 g / L. First, selenium powder solution is added to sodium molybdate solution. Then, BiFeO3 is added dropwise to the mixture of selenium powder solution and sodium molybdate solution. The mixture is ultrasonically stirred. After stirring, the mixture is transferred to a 100 mL high-pressure autoclave lined with polytetrafluoroethylene and heated. After washing and drying, the mixture is obtained. The mass concentration of BiFeO3 in sodium molybdate solution is 10-16.67 g / L.
2. The preparation method of the BiFeO3 / MoSe2 photocatalytic material according to claim 1, characterized in that, In step (1), the water bath temperature is 60-80℃ and the time is 10-14h, and the calcination temperature in step (1) is 500-550℃ and the time is 2-4h.
3. The preparation method of the BiFeO3 / MoSe2 photocatalytic material according to claim 1, characterized in that, In step (1), the mass concentrations of bismuth nitrate pentahydrate and ferric nitrate nonahydrate in nitric acid are 200–400 g / L and 200–400 g / L, respectively, and the mass concentration of the nitric acid solution in step (1) is 933–1065 g / L.
4. The preparation method of the BiFeO3 / MoSe2 photocatalytic material according to claim 1, characterized in that, In step (1), the volume ratio of nitric acid to ethylene glycol is 1:1, and in step (2), the volume ratio of sodium molybdate solution to selenium powder solution is 3:
1.
5. The method for preparing the BiFeO3 / MoSe2 photocatalytic material according to claim 1, characterized in that, In step (2), the stirring time at room temperature and ambient temperature is 10-30 min, and the ultrasonic stirring time is 20-40 min.
6. The method for preparing the BiFeO3 / MoSe2 photocatalytic material according to claim 1, characterized in that, The heating temperature in step (2) is 200-220℃ and the time is 20-24h. The drying temperature in step (2) is 60-80℃ and the time is 10-12h.
7. A BiFeO3 / MoSe2 photocatalytic material, characterized in that... It is prepared by the preparation method according to any one of claims 1 to 6.
8. The application of the BiFeO3 / MoSe2 photocatalytic material according to claim 7 in the photocatalytic synthesis of hydrogen peroxide.
Citation Information
Patent Citations
Preparation method of Co3O4 / BiFeO3 heterojunction photocatalyst and application thereof in reduction of hexavalent chromium
CN109289859A
Preparation method and application of g-C3N4 / Ag3PO4 / BiFeO3 composite visible-light-driven photocatalyst
CN113578368A